The Role of UN Peace Operations in Security Sector Reform and the Relationship with the Protection of Civilians - Sprik, Lenneke; Giblin, Jennifer; Gilder, Alexander (My University, 2022)
Security sector reform and the protection of civilians are regular features within United Nations (UN) peace operations. However, the two areas are often distinct from one another in the mandates of missions. What then is the relationship between Security Sector Reform (ssr) and the Protection of Civilians (PoC) in contemporary missions and how does ssr impact PoC? This article aims to draw out this relationship by conducting a comparative case study analysis based on three missions that all combine a ssr and PoC mandate: the United Nations Multidimensional Integrated Stabilization Mission in Mali (minusma), the United Nations Multidimensional Integrated Stabilization Mission in the Central African Republic (minusca) and the United Nations Organization Stabilization Mission in the Democratic Republic of the Congo (monusco). The case studies provide a variety of examples which demonstrate elements of both convergence and divergence in the implementation of ssr and PoC. With ssr often taking place in a context of armed conflict, the current focus on human rights training and accountability is insufficient as the missions fail to achieve long-term ssr goals and instead must prioritise PoC due to the actions of the host states.
Keywords: Peacekeeping; security sector reform; protection of civilians